2019
DOI: 10.1080/0145935x.2019.1614906
|View full text |Cite
|
Sign up to set email alerts
|

Communal Orientation, Benefit-finding, and Coping among Young Carers

Abstract: A substantial body of research documents the impact of informal care on adult caregivers' wellbeing, but little is known of the experiences of young carers who attend postsecondary schools in Canada. Despite the estimated 1.25 million young people ages 15-24 assuming caregiving roles in Canada, young carers are a hidden and largely unsupported demographic in Canada. To gain a better understanding of young caregiving in Canada, the current study explores the role of communal orientation, benefit-finding, life s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Experienced benefits in response to caring have been documented across diverse populations of young people, including current and former carers, different age groups, and varying characteristics of the person cared for (e.g. Areguy et al, 2019;Kallander et al, 2018;Pakenham et al, 2007;Shifren et al, 2014). Moreover, recent research has suggested that more perceived caring responsibility is associated with a higher level of benefit finding in young carers (Pakenham & Cox, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Experienced benefits in response to caring have been documented across diverse populations of young people, including current and former carers, different age groups, and varying characteristics of the person cared for (e.g. Areguy et al, 2019;Kallander et al, 2018;Pakenham et al, 2007;Shifren et al, 2014). Moreover, recent research has suggested that more perceived caring responsibility is associated with a higher level of benefit finding in young carers (Pakenham & Cox, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis revealed that caring responsibilities could have a negative impact on student carers physical and mental health (Crandall et al 2014;Morgan 2019;Soliz and Merai 2018;Van Der Werf et al 2019). Research found that student carers experience lower wellbeing than those who do not have caring responsibilities (Areguy et al 2019);…”
Section: Theme 1: Impact Of Caring On Student Carer Physical and Ment...mentioning
confidence: 99%
“…Kettell (2020) found that student carers relied on their peers to take class notes for them and keep them up to date; this supported the student to continue their studies. Interestingly, one study found a high level of instrumental support (e.g., seeking and/ or receiving support from other people) was associated with higher ratings of benefit-finding (Areguy et al 2019), and used previous research to highlight that benefit-finding relates to positive health outcomes. In the same study, the authors found that student carers with greater communal orientation were better able to find benefits in their role because of this instrumental support.…”
Section: Theme 6: Informal Supportmentioning
confidence: 99%
“…In the United Kingdom (UK) a young carer is defined as a young person aged under 18 years who provides or intends to provide care for another person (HM Government 2014). However, definitions vary between countries and studies resulting is estimates of the proportion of young carers varying from 2% in the UK up to 50% in one Canadian study (Areguy et al 2019, Office of National Statistics 2013. Joseph et al (2020) in their overview of studies concluded that 2-8% of children and adolescents are young carers.…”
Section: Introductionmentioning
confidence: 99%